Present and future of the dialogue between Theology of Creation and Science - Martínez Baigorri, Javier (Razón y fe, 2019)
In recent decades, a group of scientists and theologians has opened the way to the renewal of the Theology of Creation. It is important to introduce theological models that update theological reflection in the light of science. Some lines of work opened by these authors are outlined: descending causality as a model of continuous creative action and God’s relationship with creation through time. We find in these fields, although they need more development, an example of how to develop the future of the Theology of Creation.